Study on the Thermodynamic Spectroscopy Methods of Dopamine with V(V), Ni(II) and Co(III) - Nasirian, A.; Keshavarz, M. (Asian Journal of Chemistry, 2012)
Dopamine is a member of ketcol amine groups. Dopamine is a hormone in body and acts as a nerve transferor in brain. Shortage of dopamine can lead to Parkinson disease so thermodynamic study using spectroscopy methods is an important issue for recognition of dopamine in blood and biological and pharmaceutical liquids. In this study, the interactions of water soluble metallic ions of V(V), Ni(II) and Co(III) with dopamine have been investigated using UV-VIS spectroscopy technique, SQUAD program as well as thermodynamic studies. The obtained results indicate the formation of 1:1 complex of V(V), Ni(II) and Co(III) with dopamine. Doing experiments at six different temperatures and analyzing the data helped us to thermodynamic analysis based on Vant Hoff equation. Results showed that reaction is exothermic and process is enthalpy and entropy driven.